2022
DOI: 10.3390/ijerph19159683
|View full text |Cite
|
Sign up to set email alerts
|

Emission Trading System, Carbon Market Efficiency, and Corporate Innovations

Abstract: Taking China’s emission trading system (ETS) pilot in 2013 as a quasi-natural experiment, this paper uses the difference-in-differences (DID) models to study whether the regional pilot ETS can promote technological innovation in enterprises. In addition, this paper examines the influence mechanism of the ETS innovation effect, with a focus on three key dimensions of the carbon market efficiency: market price effectiveness, market product diversity, and market order normativity. The results show that the pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…While the Renewable energy Trading system balances real economic growth and a low-carbon economy, it opens a huge Carbon Market. In terms of their legal systems, US laws are more mature in regulating Carbon Markets [22]. The EU member states have different laws and regulations.…”
Section: The Situation Of Policy Dimension In the International Carbo...mentioning
confidence: 99%
“…While the Renewable energy Trading system balances real economic growth and a low-carbon economy, it opens a huge Carbon Market. In terms of their legal systems, US laws are more mature in regulating Carbon Markets [22]. The EU member states have different laws and regulations.…”
Section: The Situation Of Policy Dimension In the International Carbo...mentioning
confidence: 99%
“…In China's case, studies agree with the ineffective application of the carbon financial mechanism, which is believed to be one of the important reasons behind the lower carbon price in its pilot markets [35]. Zhu et al found that when the gap between the carbon price and the marginal abatement cost (MAC) of CO 2 is smaller, the carbon financial derivatives are more abundant [25]. Liu C et al took regression tests and found an empirically significant relationship between the average price of carbon emission rights and the total amount of regional carbon emissions in a six pilot Chinese markets but failed to find significant and negligible relationships between the issuance amount of green bonds and the transaction amount of carbon emission rights [36].…”
Section: Carbon Financial Mechanismmentioning
confidence: 94%
“…It suggests that free allowances are preferred for an ETS in the early stages. In order to have effective prices, dynamic allocation (e.g., outputbased free allowances and mixed allowance) is extensively discussed on the cost-contained, price-responsive allowance supply [25,26] and on the capacity of explicit carbon pricing to drive significant abatements [27].…”
Section: Carbon Total Emission Trading Mechanismmentioning
confidence: 99%
“…Porter & Linde (1995) [7] proposed the "Porter Hypothesis", which argues that enterprises' environmental protection investment can prompt companies to increase innovation in and the use of clean technologies, offsetting environmental protection costs and achieving a win-win situation for both environmental governance and economic profitability. Research on corporate environmental governance behaviors such as corporate environmental disclosure [8], environmental performance [9,10], and technological innovation [11][12][13] has received increasing attention from scholars.…”
Section: Literature Reviewmentioning
confidence: 99%